Animal names of hydronymic origin: Slovenian Sebin/Sabin/Savin and Sava - Furlan, Metka (Jezikoslovni zapiski, 2018)
Slovenian and Croatian proper names for cattle with the stem Sav‑ may reflect a Slavic onomastic tradition of the transfer of animal names from hydronyms.